On the Existence and Uniqueness of Solution for the Fractional Fredholm Integro-Differential Equation through the Fractional Variational Orthogonal Collocation method with Mamadu-Njoseh orthogonal basis functions - Tsetimi, Jonathan; Mamadu, 2Ebimene James (European Journal of Applied Sciences, 2021)
In this article, we present a detailed analysis on the existence and uniqueness of solution for the fractional Fredholm integro-differential equation (FFIDE) via the fractional variational orthogonal collocation method (FVOCM) with Mamadu-Njoseh orthogonal basis functions. Relevant theorems were formulated and proven to show that there exist a solution for the problem FFIDE through the FVOCM, and the solution is shown to be unique.